Boosted Reading Comprehension Using PQRST (Preview Question Read Summarize Test) with Images and Short Videos - Nurzakiyah, Sisca; Wiyaka, Wiyaka; Senowarsito, Senowarsito (Pedagogia : Jurnal Pendidikan, 2025)
The purpose of this study was to compare the ability to read narrative texts between students taught using the integrated PQRST method with STAD assisted by short videos and pictures series, and to describe students' perceptions of the use of the two different methods. The research method used in this study is a quasi-experimental study. This study will be conducted at SMP Negeri 1 Tahunan Jepara Regency, Central Java. The subjects of the study were students of class 9B as the experimental class and class 9C as the control class. Data collection used tests and questionnaires. Data analysis used descriptive analysis and independent sample t-test. Based on the results of the study, it can be concluded that the ability to read narrative texts of students taught using the PQRST method oriented to the STAD model assisted by short videos is better than students taught using the PQRST method oriented to the STAD model assisted by pictures series. These results indicate that the PQRST method oriented to the STAD model assisted by short videos is effective in improving students' ability to read narrative texts. Highlights: Method Comparison: The study found that short video-assisted learning significantly improved narrative reading skills over picture series. Effective Combination: Integrating PQRST with STAD and short videos forms a potent approach to enhance students’ comprehension. Student Perception: Students responded positively to short video integration, highlighting its effectiveness and engagement. Keywords: Narrative Text, Short Videos, Pictures Series